Population persistence within an extreme environment: genetic connectivity of the coral reef fish Lutjanus ehrenbergii across the Arabian Peninsula - Griffiths, Marylka (2016)
Resolving the pattern of genetic connectivity in the ocean is necessary for fishery management, conservation and in answering key questions in evolutionary ecology. A main theme in terms of connectivity in the ocean is how environmental and oceanographic factors shape population structure. Such questions weave an understanding of genetic and demographic patterns with the importance of environmental gradients and oceanographic processes. This project is focused on the Arabian Gulf, which has the largest thermal SST range globally, whilst also showing extremes in salinity. This system is connected to the Gulf of Oman, via the Strait of Hormuz, which has comparatively more benign oceanic conditions which are expected for a typical tropical marine system. Researchers postulated that an environmental gradient across the Arabian Peninsula that may act as a potential barrier to survival and larval dispersal of fish communities across this region. I will show how populations of the coral reef associated fish, Lutjanus ehrenbergii, are shaped across the Arabian Peninsula, using genetic analysis of mitochondrial DNA to describe patterns of genetic similarity. The pattern of environmental conditions presented that the Strait of Hormuz contains conditions that are an intermediate between the Arabian Gulf and the Gulf of Oman. Yet, considering the presence of this ‘filter’ or environmental gradient, this area did not act as a geographic break in population structure across the Arabian Peninsula. Overall no significant genetic differentiation occurred between populations grouped as; the Arabian Gulf, the Strait of Hormuz and the Gulf of Oman. Haplotypes, and defined clade groupings were found spread over the entire Arabian Peninsula which can be interpreted as a pattern of genetic connectivity. However, there were 3 clade groupings composed of few haplotypes which were found in restricted areas, which could signify a degree of restriction of clades. In the analysis between sampling locations, many populations showed no significant departure from 0. However, in the markers control region and COI significant moderate genetic differentiation was revealed in a small number of populations. This genetic differentiation did not fit with a spatial or environmental pattern. This could suggest a pattern of chaotic genetic patchiness in the region. The predominant lack of genetic subdivision can be interpreted as an overall pattern of connectivity in the region which could be due to the initial movement and colonisation of the Arabian Gulf from the Indian Ocean. Larval dispersal projection gave a preliminary description of the movement of a generic fish larva across the Arabian Peninsula. The results showed a high level of self-recruitment, with little connectivity. This pattern shows that passive particle movement via oceanographic forces leads to restricted movement of larvae and showed little connectivity between neighbouring regions. A contemporary pattern of restricted movement would be expected to lead to genetic isolation of populations. This provides a good starting point, which can be continued to model how stochastic movement occurs over a longer period of several years, and can be combined with genetic analysis in the future.